2019
DOI: 10.1097/aog.0000000000003357
|View full text |Cite
|
Sign up to set email alerts
|

Medication Abortion Provided Through Telemedicine in Four U.S. States

Abstract: OBJECTIVE: To assess outcomes of medication abortion provided through telemedicine compared with standard medication abortion at Planned Parenthood health centers in four U.S. states. METHODS: In this retrospective cohort study, we analyzed electronic health records for patients receiving telemedicine compared with standard medication abortion at 26 health centers in Alaska, Idaho, Nevada, and Washington from April 2017 to March 2018. All patients had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…Similar developments may have contributed to the increase in clinics in Alaska and Washington. 20 The overall number of clinics in the Midwest and the South declined. Texas had the largest drop, losing seven clinic facilities between 2014 and 2017.…”
Section: Changes In Clinic Numbers Abortion Rates and Policy Contextmentioning
confidence: 99%
“…Similar developments may have contributed to the increase in clinics in Alaska and Washington. 20 The overall number of clinics in the Midwest and the South declined. Texas had the largest drop, losing seven clinic facilities between 2014 and 2017.…”
Section: Changes In Clinic Numbers Abortion Rates and Policy Contextmentioning
confidence: 99%
“…Perceived usefulness is defined as the degree to which an individual believes that using a particular technology would be beneficial, and both OFCs and reproductive hormone SCTs may be perceived as useful. Indeed, telemedicine allows health care providers to offer the same services they provide to patients during in-person consultations, 18,19 and studies directly comparing phone-or video-based consultations to inperson health care consultations suggest similar patient outcomes and satisfaction. 22,23 Together, this suggests that online consultations may be as useful as traditional in-person health care consultations.…”
Section: Tam: Perceived Usefulness and Perceived Ease Of Usementioning
confidence: 99%
“…Perceived ease of use is defined as the degree to which an individual believes that using a particular technology would be free from effort, and both OFCs and reproductive hormone SCTs may also be perceived as easy to use. Indeed, past research has found that both online consultations 18,30 and SCTs 21 for a wide range of health services circumvent the geographic, financial, and time-based limitations of in-person health care services. 8,31 Both OFCs and reproductive hormone SCTs can also be used discreetly and in the privacy of one's own home, thus potentially mitigating some of the stigma felt by women pursuing fertility care.…”
Section: Tam: Perceived Usefulness and Perceived Ease Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…In rural communities, and to increase privacy for all, a clinic based telemedicine service could be set up, whereby medical consultation with a clinician takes place remotely and drugs are provided by a pharmacy or even by mail. Good evidence suggests that these services are safe, effective, and acceptable to patients 1415…”
Section: A Patient Centred Servicementioning
confidence: 99%